A Decade of Medical Pharmacology Speciality and Ph.D. Theses in Turkey: A Comparative Study - Ongun, Mert Can; Bariskaner, Hulagu (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives This study aimed to analyse the characteristics and publication trends of medical pharmacology specialty and Ph.D. theses. Materials and Methods Medical pharmacology theses published in Turkey between 2010 and 2020, were included. Data on the study topic, funding source and publication year, were collected from the National Thesis Center's online archive. A follow-up search was conducted to evaluate the publication status of the theses, using databases such as the Web of Science, PubMed, Google Scholar and TR-Dizin. Results Our study found that the proportion of specialty theses that did not receive funding was higher, compared to Ph.D. theses (47.9% and 33.3% respectively, p=0.04). In both the medical specialty and Ph.D. theses, neuropharmacology was the most common study topic at 31.1% and 41.5% respectively, followed by cardiovascular pharmacology at 21.1% and 19.5%, respectively. However, clinical pharmacology was a more prevalent topic in medical specialty theses (23.9%) than in Ph.D. theses (7.3%). About 48% of specialty and 60% of Ph.D. theses were published in academic journals. Furthermore, 73.5% of specialty and 71.6% of Ph.D. thesis articles were indexed in Science Citation Index Expanded (SCI-E). Conclusion We noted differences in funding status and study topics between medical pharmacology specialty and Ph.D. theses. High publication rates in SCI-E journals indicate the impact of these theses in medical pharmacology. Our data showed a consistent focus on neuropharmacology and cardiovascular pharmacology topics in these theses, with an increasing attention on Clinical Pharmacology. Our findings provide guidance for postgraduate students, advisors and educational planners.
Keywords: Pharmacology; Ph.D. Thesis; Specialty Thesis; Research Trends; Bibliometric Analysis; Publication Status